The welfare impact of rising food prices - Ralitza Dimova (IZA World of Labor, 2015)
Dramatic food price spikes in recent years have stimulated debate on the welfare implications of food price risk. According to the Food and Agriculture Organization of the United Nations, the number of undernourished people in sub-Saharan Africa rose to a record 265 million in 2009. There is a gradually developing policy consensus in favor of income redistribution to the poor in developing countries hit by the food price crisis. This recommendation makes sense when the poor are net food consumers, but it ignores the possibility that some poor people are net producers of food and so are likely to benefit from rising food prices.
Keywords: D6; D31; I3; 330; rising food prices; labor and income generating strategies in the rural tropics; poverty; inequality